Evaluation on Expressions for Optimum Intermediate Condition of Two-Stage Vapor Compression Refrigeration Cycle - Himsar Ambarita (IPTEK The Journal for Technology and Science, 2018)
Mathematical expressions for estimating the optimum intermediate condition of two-stage vapor compression refrigeration cycle have been investigated. The objective is to evaluate the expressions for optimum intermediate condition (pressure or temperature) for maximum COP. A set of governing equations on two-stage vapor compression refrigeration cycle are developed and solved numerically. The two-stage cycle is analyzed using commonly used refrigerants for air-conditioning use, they are R12, R22, and R134a. There are six expressions for optimum intermediate condition found in literature. These expressions are divided into two group, expression for optimum pressure and expression for optimum temperature. These expressions are evaluated using the developed model. The results show that deviation of the expressions for optimum pressure can be up to 18.38%. On the other hand, the maximum deviation for optimum temperature is only 6.74%. This fact suggests that expressions for optimum temperature are better than pressure one. However, the expressions found in literature only specific for a particular refrigerant. Those can’t be used for all refrigerants.